2020
DOI: 10.1002/app.50012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crosslinked polycarboxylate superplasticizers with varied structures on cement dispersion performance

Abstract: In order to investigate the effect of double bond content in the crosslinkers on the performance of superplasticizers, three different crosslinked polycarboxylate superplasticizers were synthesized herein with various respective crosslinkers. Their impacts on the fluidity, absorption, and hydration behavior of cement systems were studied. The results showed that the polymer, which was synthesized using a crosslinker with four double bonds and five/six double bonds, had higher fluidity and the highest fluidity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…At a fixed molecular weight, the surface-occupied area became smaller for star-shaped PCEs with an increase in arm numbers, resulting in an increase in the adsorption free energy. In addition, many papers have reported cross-linked PCEs with different cross-linking monomers [142][143][144][145][146][147] with varied numbers of double bonds. Some reports have shown that slight cross-linking can improve the adsorption and thus the initial flowability of cement paste.…”
Section: Topological Structure and Polymer Molecular Framementioning
confidence: 99%
“…At a fixed molecular weight, the surface-occupied area became smaller for star-shaped PCEs with an increase in arm numbers, resulting in an increase in the adsorption free energy. In addition, many papers have reported cross-linked PCEs with different cross-linking monomers [142][143][144][145][146][147] with varied numbers of double bonds. Some reports have shown that slight cross-linking can improve the adsorption and thus the initial flowability of cement paste.…”
Section: Topological Structure and Polymer Molecular Framementioning
confidence: 99%
“…Hyperbranched PCEs were first introduced and prepared by Hamada in 2006 and subsequently received a great deal of research attention. Then, hyperbranched PCEs with different structures have been synthesized successively. Ran et al synthesized the main chain dendritic hyperbranched PCEs via in situ redox polymerization, which had compact structures and increased the thickness of the adsorption layer. However, more adsorption was needed to cover the same surface area of cement particles, showing poor dispersion ability for cement .…”
Section: Introductionmentioning
confidence: 99%